Examining fatigue for bilingual/multilingual students who are deaf or hard of hearing through the framework of universal design for learning - Rohatyn-Martin, Natalia K.; Hayward, Denyse V. (My University, 2022)
In current educational contexts, Deaf or hard of hearing (D/HH) students are being educated in inclusive classrooms. However, academic and social outcomes for these bilingual or multilingual students remain highly variable indicating that meeting the needs for students who are D/HH continues to be challenging for many educators. Many D/HH students are reporting high levels of fatigue throughout their school day. To ensure the diverse cultural and linguistic backgrounds of students are being met, a more flexible approach needs to be considered to address barriers described by D/HH students. As such, the authors use the Universal Design for Learning framework to discuss fatigue for students who are D/HH in inclusive contexts, particularly those who are bilingual/multilingual.
Keywords: deaf; hard of hearing; education; universal design for learning